Effectiveness of NPK Fertilizer and Gibberellic Acid (GA₃) Plant Growth Regulator on the Growth and Yield of Long Bean (Vigna sinensis L.) - Inne Martina Puspita Sari; Pangesti Nugrahani; Puji Lestari Tarigan (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Long bean (Vigna sinensis L.) is a valuable vegetable commodity recognized for its high nutritional value; however, its production in Indonesia has declined. This decrease can be attributed to improper cultivation techniques. To enhance production, strategies such as NPK fertilization and the application of growth regulators, specifically gibberellic acid (GA3), can be employed to improve yields. The combination of these two methods has the potential to improve both the growth and yield of long beans. This study employed a randomized complete block design (RCBD) with two factors, where each treatment combination was replicated three times. Data analysis was conducted using analysis of variance (ANOVA). This research aims to provide insights and recommendations regarding the most effective doses of NPK fertilizer and GA3 concentrations to enhance growth and yield. Specifically, it seeks to determine the optimal concentration of GA3 that promotes the growth and yield of long bean plants. The combination of NPK fertilizer and GA3 had a significant influence on the growth and yield of long bean plants. The treatment of NPK at 15 g/plant combined with GA3 at 100 ppm resulted in increased plant height, while NPK at 5 g/plant combined with GA3 at 100 ppm led to a higher number of fruits. Additionally, the combination of NPK at 15 g/plant and GA3 at 150 ppm significantly increased pod weight. Furthermore, the individual treatments of NPK at 15 g/plant and GA3 at concentrations ranging from 100 to 150 ppm also positively affected the growth and yield of long bean plants.